Penguatan Strategi Pemasaran Digital untuk Meningkatkan Daya Saing UMKM - Siti Marwati; Ulul Absor; Desy Maola Ayu Saputri; Ilham Akbar Ashari; Wynne Inayah Ekasari; Asmanisa Rahmawati; Mahardian Mustiko Nugroho; Hari Tri Wibowo; Muamar Riza Pahlevi; Faizal Yudhi Nugroho (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The development of information and communication technology has driven a shift in marketing patterns from conventional methods to digital-based marketing. However, many Micro,Small, and Medium Enterprises (MSMEs) have not yet optimally utilized digital media as a means of promotion and business development. This community service activity aims to improve the knowledge and skills of MSMEs in implementing digital marketing strategies to increase business competitiveness. The activity implementation method is carried out through the stages of observation, socialization, training, direct practice, mentoring, and evaluation. The material provided includes digital marketing concepts, the use of business social media, promotional content creation, product branding strategies, and the use of marketplaces as a marketing tool. Evaluation of the activity was carried out through pre-tests, post-tests, observations, and participant satisfaction questionnaires. The results of the activity showed an increase in participants' understanding and skills in managing digital marketing. The program's success rate reached 85.6%, demonstrated by increased participants' ability to create promotional content, manage business social media, and utilize marketplaces for product marketing. In addition, participants demonstrated a change in mindset to be more adaptive to the use of digital technology in business development. This activity has a positive impact on increasing the capacity of MSMEs to face business competition in the digital era. Therefore, ongoing support and monitoring are necessary to ensure optimal and sustainable implementation of digital marketing strategies.